An Analysis of Narrative, Music, and Sound in the Radio Adaptation of D.Natsagdorj’s Story Khuduu Taliin Üzesgelen - Sanzaijav, Basbish; Ganbaatar, Nandinbilig (Mongolian Journal of Arts and Culture, 2025)
Since its inception, Mongolian radio has created radio art productions based on various literary genres, establishing a unique artistic form that reinterprets and transmits literary works in aural form. This study focuses on the musical radio adaptation of the renowned writer D.Natsagdorj’s short story “Khuduu Taliin Üzesgelen” preserved in the Golden Archive of the Mongolian National Public Radio. The research aims to examine how the narrator’s perspective, music, and the semiotic use of sound enrich the meaning and influence the listener’s psychology. The study applies methodologies from adaptation theory, narratology, media theory, and semiotic analysis to compare and analyze the differences in narrative, storytelling, and artistic devices between the original text and its radio adaptation. The results reveal that the harmonious combination of music, sound effects, and narration in the radio adaptation deepens the original meaning, effectively conveys the atmosphere of events and characters’ emotions, and stimulates the imagination and emotional engagement of the audience. Radio adaptations of literary works not only transmit the original texts but also recreate them, offering listeners new experiences and forms of artistic expression. Д.Нацагдоржийн “Хөдөө талын үзэсгэлэн” өгүүллэгийн радио хувиргал дахь хүүрнэл ба хөгжим, дуу чимээний утгын шинжилгээ Хураангуй: Монголын радио анх үүссэн цагаасаа уран зохиолын төрөл зүйлд тулгуурлан радио уран сайхны бүтээлүүдийг туурвисаар ирсэн нь утга зохиолын бүтээлийг сонсголын урлагт нийцүүлэн дахин бүтээх, дамжуулах өвөрмөц урлагийн хэлбэрийг бий болгосон. Энэхүү судалгаанд Монголын Үндэсний олон нийтийн радиогийн “Алтан сан хөмрөг”-т хадгалагдаж буй их зохиолч Д.Нацагдоржийн “Хөдөө талын үзэсгэлэн” өгүүллэгээр хийсэн хөгжимт радио зохиомжийг сонгон авч, хүүрнэн өгүүлэгчийн байр суурь, хөгжим, дуу чимээний семиотик хэрэглээ хэрхэн утга агуулгыг баяжуулж, сонсогчийн сэтгэл зүйд нөлөөлж буйг судлахыг зорив. Судалгаанд адаптаци, нарратологи, медиа онол, семиотик шинжилгээний арга зүйг ашиглаж, эх зохиол болон радио хувиргалын өгүүлэмж, хүүрнэл, уран сайхны хэрэглүүрийн ялгааг харьцуулж, шинжилгээ хийсэн болно. Судалгааны үр дүнд радио зохиомжид хөгжим, дуу чимээ, хүүрнэл гурвын зохистой хослол нь эх зохиолын утга агуулгыг гүнзгийрүүлж, үйл явдлын уур амьсгал, дүрийн сэтгэл хөдлөлийг оновчтой илэрхийлж, сонсогчдын төсөөлөл, сэтгэл хөдлөлийг өдөөж байгааг ажиглав. Уран зохиолын радио хувиргал нь эх зохиолыг дамжуулахаас гадна түүнийг дахин бүтээж, сонсогчдод шинэ мэдрэмж, уран сайхны илэрхийллийн шинэ хэлбэрийг бүрэлдүүлж байна. Түлхүүр үгс: радио зохиомж, өгүүлэгч, хөгжим, семиотик